The Relationship Between PMR Students' Knowledge Level and Self Efficacy in Providing First Aid for Splint Dressing - Azizah, Rahmah Iva; Gaghauna, Eirene E M; Rahman, Subhannur; Tasalim, Rian (Indonesian Journal of Global Health Research, 2024)
Fracture is an emergency that requires immediate help to reduce the threat of danger to the victim, one of the causes of fractures is traffic accidents. Knowledge is a supporting factor for a person's self-efficacy in providing first aid in an accident that must be known by all groups, including high school students (PMR members). Objective to determine the relationship between the level of knowledge of PMR students to self-efficacy in providing first aid in bandage at SMAN 3 Banjarmasin. Method using a quantitative method with a cross sectional approach. The research sample of 36 people was then carried out the Chi-Square test. Based on the results of knowledge analysis on self efficacy, it showed a p-value of 0.01 <0.05 which means that there was a significant relationship between PMR students' knowledge and self efficacy in providing first aid for splint dressing. There needs to be follow-up and coordination by the school in providing first aid materials to students in a sustainable manner, with good knowledge, the self-efficacy of students in providing first aid is also good.